Prevalence of pneumoconiosis and spirometric findings in underground mining workers in cundinamarca, Colombia (2019)
Introduction: Coal worker’s pneumoconiosis is caused by the inhalation of coal dust and its accumulation in the lungs after several years of exposure. Objective: To determine the prevalence of pneumoconiosis in underground mining workers exposed to coal dust in Cundinamarca, Colombia, and its association with their spirometry results and respiratory symptoms. Materials and methods: Cross-sectional study conducted on 215 workers who were administered a questionnaire on respiratory symptoms. For each worker a chest radiograph was taken according to the criteria of the International Labor Organization. Information on the workers’ socio-demographic characteristics, smoking habits, and spirometry results was included. Results: The average age was 45.5 ± 9.4 years and the average length of employment was 21.7±10.0 years. Expectoration was the symptom most frequently reported (73.5%). Regarding spirometry results, a normal pattern was observed in 89.8% of the sample, while obstructive and restrictive patterns were found in 5.1% and 3.7% of the subjects, and 0.5% had a peripheral airways dysfunction pattern. The prevalence of pneumoconiosis was 42.33%. FEV1/FVC ratio (81.75 vs. 83.74, p=0.045) and FF25-75% (84.96 vs. 91.95, p less than 0.001) mean values were significantly lower in workers with pneumoconiosis. Conclusion: Pneumoconiosis was highly prevalent in the study population and its diagnosis was associated with spirometry results (FEV1/FVC and FEF25.75%); bearing in mind that currently there are not effective treatments for this disease, it is necessary to implement control and prevention strategies aimed at reducing occupational exposure to coal dust and, this way, prevent its occurrence. © 2019, Universidad Nacional de Colombia. All rights reserved.